Retinopathy and microalbuminuria are common microvascular complications in cystic fibrosis-related diabetes. (October 2020) - Kempegowda, Punith; Sunsoa, Harbinder; Chandan, Joht S.; Quinn, Lauren M.; Amrelia, Prashant M.; Atta, Syed Noman; Amir, Sidrah; Teh, Yee Suh; Chaudhry, Sabba; de Bray, Anne; Rashid, Rifat; Whitehouse, Joanna L.; et al.
Aims: To study the prevalence of microvascular complications and renal changes associated with cystic fibrosis-related diabetes (CFRD). Methods: This retrospective cohort study was conducted at the West Midlands Adult Cystic Fibrosis centre, United Kingdom. Data regarding age, sex, microalbuminuria, retinopathy neuropathy, and biochemical results were collected for all people with CFRD who had an annual review from 1 January 2018 to 31 December 2018 at the centre. Descriptive statistics were analysed using STATAv15.1. Results: A total of 189 patients were included, of which 56.6% were male and median age (interquartile range) was 33 (27–39) years; 79.4% (150/189) had their annual review in 2018. Those with a biochemically impaired renal function numbered 7.2% (13/180) and 22.7% (32/141) had microalbuminuria; 17.2% (10/58) had diabetes related retinopathy. No one in our cohort had diabetic ulcers; however, 10.3% (13/126) had absent foot pulses. Conclusion: We found a higher prevalence of microalbuminuria compared with retinopathy in a large cohort of cystic fibrosis adults. This study demonstrates the need for regular specialist follow-up to facilitate early identification of such complications and a long-term prospective cohort to understand underlying mechanisms.